Structural steel and preparation method thereof
By controlling the ratio of V and N and the formation of vanadium carbonitride reinforcing phases by rare earth elements in SAE1055 structural steel, the problem of insufficient strength and fatigue performance of wheel hub bearing units was solved, and high-strength and high-elongation structural steel was prepared.
Patent Information
- Application Number
- CN202411330667.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing mechanical properties of SAE1055 structural steel cannot meet the requirements of wheel hub bearing units, and its strength and fatigue performance need to be improved.
By controlling the ratio of microalloying elements V and N in steel to 8–10:1, and adding rare earth elements V or Nb to form a dispersed vanadium carbonitride strengthening phase, combined with strict control of the smelting and rolling process, a pearlitic and ferritic structural steel with uniform microstructure can be prepared.
It significantly improves the tensile strength and yield strength of structural steel, increases elongation, improves bending fatigue performance by more than 80%, and improves grain size grade by 1 level or more.
Smart Images

Figure CN119433375A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of steel preparation, and in particular to structural steel and a preparation method thereof. Background Art
[0002] Steel is an essential component of the construction industry, with characteristics such as high strength, versatility and durability. Structural steel is a type of steel product that is specifically designed and manufactured for load-bearing structures. Structural steel is often alloyed with other elements (such as carbon, manganese and chromium) to increase its strength, ductility and corrosion resistance. Structural steel's excellent strength-to-weight ratio, durability and versatility make it an indispensable material for a variety of projects. Steel structures provide the necessary support and stability to make ambitious architectural and engineering designs a reality. Structural steel's ability to withstand heavy loads and resist deformation ensures the safety and longevity of the structure, making it the first choice for projects where structural integrity is critical.
[0003] With the development of the times and high-quality technical requirements, the mechanical properties of the existing SAE1055 structural steel cannot meet the needs of the wheel hub bearing unit, so a technology that can improve the mechanical properties of SAE1055 structural steel is needed. Summary of the invention
[0004] To solve at least one problem in the background technology, the present invention provides a structural steel and a method for preparing the same.
[0005] In a first aspect, the present invention provides a structural steel comprising, by mass percentage:
[0006] 0.2.~0.60wt% C, 0.15~0.45wt% Si, 0.6~0.90wt% Mn, 0.10~0.20wt% Cr, 0.10~0.20wt% Ni, 0.01~0.05wt% Al, 0~0.014wt% N, 0.05~0.15wt% rare earth elements, the balance being iron and unavoidable impurity elements;
[0007] The rare earth element includes V or Nb;
[0008] The structural steel structure includes a base phase and a strengthening phase, the strengthening phase is dispersed in the base phase, the base phase includes pearlite grains and ferrite grains, the size of the pearlite grains is 25-35 μm, and the strengthening phase includes vanadium carbonitride.
[0009] Preferably, the content of N is 0.007-0.014 wt %, and the content of the rare earth element is 0.10-0.15 wt %.
[0010] Preferably, the mass ratio of the rare earth element to the N is 8 to 10:1.
[0011] Preferably, the tensile strength of the structural steel is 799-880 MPa, the yield strength is 503-537 MPa, and the elongation is 15.7-23%.
[0012] In a second aspect, the present invention provides a method for preparing structural steel, comprising the following steps:
[0013] The iron-containing raw material is smelted, and ferrosilicon alloy, ferrochrome alloy, ferromanganese alloy and rare earth alloy are added in the steel tapping process, and the steel tapping is followed by degassing, billet casting and rolling to obtain structural steel, wherein the base phase in the structure of the structural steel has a strengthening phase of vanadium carbonitride distributed therein;
[0014] The chemical composition of the structural steel comprises 0.2 to 0.60 wt% carbon, 0.15 to 0.45 wt% silicon, 0.6 to 0.90 wt% manganese, 0.10 to 0.20 wt% chromium, 0.10 to 0.20 wt% nickel, 0.01 to 0.05 wt% aluminum, 0 to 0.014 wt% nitrogen, 0.05 to 0.15 wt% rare earth elements, and the remainder is iron and unavoidable impurity elements.
[0015] Preferably, a slag-breaking agent is added during the smelting process, and the slag-breaking agent includes a desulfurization agent and / or a dephosphorization agent.
[0016] Preferably, the smelting further includes refining, and during the refining process, the carbon content is controlled to be 0.50-0.60wt%, the silicon content is controlled to be 0.25-0.45wt%, the manganese content is controlled to be 0.60-0.90wt%, and the chromium content is controlled to be 0.10-0.20wt%.
[0017] Preferably, the smelting further includes refining, and during the refining process, the carbon content is controlled to be 0.50-0.60wt%, the silicon content is controlled to be 0.25-0.45wt%, the manganese content is controlled to be 0.60-0.90wt%, and the chromium content is controlled to be 0.10-0.20wt%.
[0018] Preferably, in the degassing step, oxygen is controlled to be ≤8ppm and hydrogen is controlled to be ≤3ppm.
[0019] Preferably, the starting rolling temperature in the rolling process is 1050-1150° C., the rolling time is 0.5-1 h, and the rolling reduction ratio is greater than 15.
[0020] The present invention has the following beneficial effects:
[0021] 1. Through the bending fatigue test of the hub bearing unit product using the structural steel of the present invention, it is verified that the improvement of material strength significantly improves the fatigue performance of the bearing structure, and the fatigue performance of the structure is improved by more than 80%.
[0022] 2. The structural steel of the present invention has an obvious effect of refining grains, and can improve the grain size grade by 1 level or more. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The optical microstructure diagram of the structural steel of Examples 1-3 of the present invention and Comparative Example 1 at 500 magnification is shown;
[0024] Figure 2 The optical microstructure diagram of the structural steel of Examples 1-3 of the present invention and Comparative Example 1 at 100 magnification is shown;
[0025] Figure 3 The grain size grade diagram of the structural steel structure of Examples 1-3 of the present invention and Comparative Example 1 is shown;
[0026] Figure 4 A bar graph of L50% life of the hub bearing unit bending fatigue test of Examples 1-3 of the present invention and Comparative Example 1 is shown. DETAILED DESCRIPTION
[0027] The present disclosure will now be discussed with reference to several exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and thus implement the present disclosure, rather than implying any limitation on the scope of the present disclosure.
[0028] On the one hand, this embodiment discloses a structural steel and a method for preparing the same, such as Figure 1 As shown, according to the mass percentage, it includes:
[0029] 0.2.~0.60wt% C, 0.15~0.45wt% Si, 0.6~0.90wt% Mn, 0.10~0.20wt% Cr, 0.10~0.20wt% Ni, 0.01~0.05wt% Al, 0~0.014wt% N, 0.05~0.15wt% rare earth elements, the balance being iron and unavoidable impurity elements;
[0030] The rare earth element includes V or Nb;
[0031] The structural steel structure includes a base phase and a strengthening phase, the strengthening phase is dispersed in the base phase, the base phase includes pearlite grains and ferrite grains, the size of the pearlite grains is 25-35 μm, and the strengthening phase includes vanadium carbonitride.
[0032] Preferably, the content of N is 0.007-0.014 wt %, and the content of the rare earth element is 0.10-0.15 wt %.
[0033] Preferably, the mass ratio of the rare earth element to the N is 8 to 10:1.
[0034] Preferably, the tensile strength of the structural steel is 799-880 MPa, the yield strength is 503-537 MPa, and the elongation is 15.7-23%.
[0035] On the other hand, this embodiment discloses a method for preparing structural steel, comprising the following steps:
[0036] The iron-containing raw material is smelted, and ferrosilicon alloy, ferrochrome alloy, ferromanganese alloy and rare earth alloy are added in the steel tapping process, and the steel tapping is followed by degassing, billet casting and rolling to obtain structural steel, wherein the base phase in the structure of the structural steel has a strengthening phase of vanadium carbonitride distributed therein;
[0037] The chemical composition of the structural steel comprises 0.2 to 0.60 wt% carbon, 0.15 to 0.45 wt% silicon, 0.6 to 0.90 wt% manganese, 0.10 to 0.20 wt% chromium, 0.10 to 0.20 wt% nickel, 0.01 to 0.05 wt% aluminum, 0 to 0.014 wt% nitrogen, 0.05 to 0.15 wt% rare earth elements, and the remainder is iron and unavoidable impurity elements.
[0038] Preferably, the smelting further includes refining, and during the refining process, the carbon content is controlled to be 0.50-0.60wt%, the silicon content is controlled to be 0.25-0.45wt%, the manganese content is controlled to be 0.60-0.90wt%, and the chromium content is controlled to be 0.10-0.20wt%.
[0039] Preferably, the smelting further includes refining, and during the refining process, the carbon content is controlled to be 0.50-0.60wt%, the silicon content is controlled to be 0.25-0.45wt%, the manganese content is controlled to be 0.60-0.90wt%, and the chromium content is controlled to be 0.10-0.20wt%.
[0040] Preferably, in the degassing step, oxygen is controlled to be ≤8ppm and hydrogen is controlled to be ≤3ppm.
[0041] Preferably, the starting rolling temperature in the rolling process is 1050-1150° C., the rolling time is 0.5-1 h, and the rolling reduction ratio is greater than 15.
[0042] Example 1
[0043] 1) Testing the radioactive elements of scrap steel, the composition of molten iron and scrap steel, and the chemical composition of ferrosilicon, ferrochrome, ferromanganese and rare earth alloys, smelting the wastewater and scrap steel into molten iron at a smelting temperature of 1250-1350° C. and a smelting time of 5-8 hours, and adding a desulfurizer and a dephosphorization agent to control phosphorus <0.10wt% and sulfur <0.05wt% to obtain the first molten steel;
[0044] 2) The first molten steel obtained in step 1) is transferred to an EAF electric arc furnace for smelting at a temperature of 1600° C. During the steel tapping process, ferrosilicon alloy, ferrochromium alloy, ferromanganese alloy and rare earth alloy, such as vanadium, niobium and other alloying elements are added. According to the composition of the steel sample obtained by measurement, it is determined whether to add a carburizer and an alloy to control the content of alloying elements such as carbon, silicon, manganese, chromium and the like in the smelting. The content of carbon should be controlled at 0.40-0.50wt%, the content of silicon should be controlled at 0.15-0.25wt%, the content of manganese should be controlled at 0.70-0.80wt%, and the content of chromium should be controlled at 0.15-0.20wt%, to obtain a second molten steel;
[0045] 3) The second molten steel obtained in step 2) is transferred to an LF furnace for refining at a refining temperature greater than 1500° C. for a time greater than 40 min, and argon is blown and stirred to remove non-metallic inclusions by slagging and fluidity, so as to make the molten steel purer. According to the composition of the steel sample obtained by measurement, it is determined whether to add a carburizer and an alloy to control the content of alloying elements such as carbon, silicon, manganese, and chromium in the smelting, and further control the proportion of elemental components. At this time, the content of carbon element is controlled to be 0.50-0.60wt%, the content of silicon element is 0.15-0.30wt%, the content of manganese element is 0.60-0.90wt%, and the content of chromium element is 0.10-0.20wt%, as shown in Table 1, to obtain a third molten steel;
[0046] 4) placing the third molten steel obtained in step 3) in RH for vacuum degassing, maintaining the vacuum degree less than 200 Pa, and controlling the oxygen content in the air atmosphere to be less than or equal to 8 ppm, and the hydrogen content to be less than or equal to 3 ppm;
[0047] 5) The ladle obtained in step 4) is moved to a designated pouring position through a turntable, and then the molten steel is poured into a tundish, which then distributes the molten steel to various crystallizers, and the casting is cooled, solidified, and crystallized by cooling the crystallizer, and the ingot in the crystallizer is pulled out and straightened by a straightening machine to form a continuous casting ingot;
[0048] 6) placing the continuous casting billet in step 5) in a heating furnace and heating it to 1100° C., rolling the continuous casting billet after heating, with the starting rolling temperature being 1100° C., the rolling time being 0.7 h, and the rolling compression ratio being greater than 15, thereby obtaining structural steel.
[0049] The obtained structural steel was subjected to optical microstructure observation at 500x and 100x magnifications, such as Figure 1 and Figure 2 As shown in the figure, the structure is lamellar pearlite + ferrite structure, in which black is pearlite grains and white is ferrite grains. The ferrite structure directly reflects the size of the grains and the morphology of the grain distribution. Figure 3 shown.
[0050] Example 2
[0051] 1) Testing the radioactive elements of scrap steel, the composition of molten iron and scrap steel, and the chemical composition of ferrosilicon, ferrochrome, ferromanganese and rare earth alloys, smelting the wastewater and scrap steel into molten iron at a temperature of 1250°C and a smelting time of 5-8h, adding desulfurizer and dephosphorization agent, controlling phosphorus < 0.10wt% and sulfur < 0.05wt%, to obtain the first molten steel;
[0052] 2) The first molten steel obtained in step 1) is transferred to an EAF electric arc furnace converter for smelting at a temperature of 1600° C. During the steel tapping process, ferrosilicon alloy, ferrochromium alloy, ferromanganese alloy and rare earth alloy, such as vanadium, niobium and other alloying elements are added. According to the composition of the steel sample obtained by measurement, it is determined whether to add a carburizer and an alloy to control the content of alloying elements such as carbon, silicon, manganese, chromium and the like in the smelting. The content of carbon should be controlled at 0.40-0.50wt%, the content of silicon should be controlled at 0.15-0.25wt%, the content of manganese should be controlled at 0.70-0.80wt%, and the content of chromium should be controlled at 0.15-0.20wt%, to obtain a second molten steel;
[0053] 3) The second molten steel obtained in step 2) is transferred to an LF furnace for refining at a refining temperature greater than 1500°C for a time greater than 40 min, and argon is blown and stirred to remove non-metallic inclusions by slagging and fluidity, so as to make the molten steel purer. According to the composition of the steel sample obtained by measurement, it is determined whether to add a carburizer and an alloy to control the content of alloying elements such as carbon, silicon, manganese, and chromium in the smelting, and further control the proportion of elemental components. At this time, the content of carbon element is controlled to be 0.50-0.60wt%, the content of silicon element is 0.25-0.45wt%, the content of manganese element is 0.60-0.90wt%, and the content of chromium element is 0.10-0.20wt%, as shown in Table 1, to obtain a third molten steel;
[0054] 4) placing the third molten steel obtained in step 3) in a VD for vacuum degassing, maintaining a vacuum degree of less than 200 Pa, and controlling the oxygen content in the air atmosphere to be less than or equal to 8 ppm, and the hydrogen content to be less than or equal to 3 ppm;
[0055] 5) The ladle obtained in step 4) is moved to a designated pouring position through a turntable, and then the molten steel is poured into a tundish, which then distributes the molten steel to various crystallizers, and the casting is cooled, solidified, and crystallized by cooling the crystallizer, and the ingot in the crystallizer is pulled out and straightened by a straightening machine to form a continuous casting ingot;
[0056] 6) placing the continuous casting billet in step 5) in a heating furnace and heating it to 1050° C., rolling the continuous casting billet after heating, with the starting rolling temperature being 1050° C., the rolling time being 1 hour, and the rolling compression ratio being greater than 15, thereby obtaining structural steel.
[0057] The obtained structural steel was subjected to optical microstructure observation at 500x and 100x magnifications, such as Figure 1 and Figure 2 As shown in the figure, the structure is lamellar pearlite + ferrite structure, in which black is pearlite grains and white is ferrite grains. The ferrite structure directly reflects the size of the grains and the morphology of the grain distribution. Figure 3 shown.
[0058] Example 3
[0059] 1) Testing the radioactive elements of scrap steel, testing the composition of molten iron and scrap steel, testing the chemical composition of ferrosilicon, ferrochrome, ferromanganese and rare earth alloys, melting the wastewater and scrap steel into molten iron at a temperature of 1350° C. for 5-8 hours, adding desulfurizer and dephosphorizer to control phosphorus <0.10wt% and sulfur <0.05wt% to obtain the first molten steel;
[0060] 2) The obtained product of step 1) is transferred to a BOF converter for smelting at a temperature of 1650° C. According to the composition of the steel sample obtained by measurement, it is determined whether to add a carburizer and an alloy to control the content of alloying elements such as carbon, silicon, manganese, and chromium in the smelting. The content of carbon should be controlled at 0.40-0.50wt%, the content of silicon should be controlled at 0.15-0.25wt%, the content of manganese should be controlled at 0.70-0.80wt%, and the content of chromium should be controlled at 0.15-0.20wt%. In the process of steel tapping, ferrosilicon alloy, ferrochromium alloy, ferromanganese alloy and rare earth alloy, such as vanadium, niobium and other alloying elements are added to obtain a second molten steel;
[0061] 3) Transfer step 2) to LF furnace for refining, with the refining temperature greater than 1500°C and the time greater than 40min, and blow argon and stir, and remove non-metallic inclusions by slagging and fluidity, so as to make the molten steel purer, and determine whether to add carburizer and alloy to control the content of alloying elements such as carbon, silicon, manganese, chromium, etc. in the smelting according to the measurement of the steel sample composition, and further control the proportion of element composition, at this time, the content of carbon element is controlled to be 0.50-0.60wt%, the content of silicon element is 0.25-0.45wt%, the content of manganese element is 0.60-0.90wt%, and the content of chromium element is 0.10-0.20wt%, as shown in Table 1, to obtain the third molten steel;
[0062] 4) placing the product obtained in step 3) in a VD for vacuum degassing, maintaining a vacuum degree of less than 200 Pa, and controlling the oxygen content in the air atmosphere to be less than or equal to 8 ppm, and the hydrogen content to be less than or equal to 3 ppm;
[0063] 5) The ladle obtained in step 4) is moved to a designated pouring position through a turntable, and then the molten steel is poured into a tundish, which then distributes the molten steel to various crystallizers, and the casting is cooled, solidified, and crystallized by cooling the crystallizer, and the ingot in the crystallizer is pulled out and straightened by a straightening machine to form a continuous casting ingot;
[0064] 6) placing the continuous casting billet in step 5) in a heating furnace and heating it to 1150° C., rolling the continuous casting billet after heating, with the starting rolling temperature being 1150° C., the rolling time being 0.5 h, and the rolling compression ratio being greater than 15, thereby obtaining structural steel.
[0065] The obtained structural steel was subjected to optical microstructure observation at 500x and 100x magnifications, such as Figure 1 and Figure 2 As shown in the figure, the structure is lamellar pearlite + ferrite structure, in which black is pearlite grains and white is ferrite grains. The ferrite structure directly reflects the size of the grains and the morphology of the grain distribution. Figure 3 shown.
[0066] Comparative Example 1 is the existing SAE1055 structural steel, and the composition of the existing SAE1055 structural steel is shown in Table 1. The SAE1055 structural steel was subjected to optical microscopic observation at 500 times and 100 times. Figure 1 and Figure 2 As shown, the grain size grade is Figure 3 shown.
[0067] Table 1 Composition of structural steel of Example 1 and composition of structural steel of comparative example
[0068]
[0069] The mechanical properties of the structural steels of Examples 1-3 and the existing SAE1055 structural steel of Comparative Example 1 were tested under the same conditions. The mechanical properties of the structural steels of Examples 1-3 and the mechanical properties of the structural steel of Comparative Example 2 are shown in Table 2 below:
[0070] Table 2 Mechanical properties of structural steel of Example 2 and Comparative Example 1
[0071]
[0072] As shown in Table 2, the tensile strength of the structural steels of Examples 1-3 is 799-880MPa, the yield strength is 503-537MPa, and the elongation is 17.5-23%, while the tensile strength of the structural steel of the comparative example is 780MPa, the yield strength is 460MPa, and the elongation is 18%. It can be seen that the tensile strength and yield strength of the structural steels of Examples 1-3 are significantly higher than those of Comparative Example 1, and the elongation of the structural steels of Examples 1-3 is higher than that of Comparative Example 1 to a certain extent. The mechanical properties of Examples 1-3 are significantly higher than those of the comparative example, indicating the technical progress brought about by the structural steel and the preparation method thereof of the present invention.
[0073] The hub bearing units using the structural steel of Examples 1-3 were subjected to bending fatigue test L50% life. Figure 4 As shown, the bending fatigue strength of the structural steel phase of Example 3 is improved by about 80% compared with the bending fatigue strength of SAE1055 structural steel.
[0074] The present invention controls the ratio of microalloying elements V to N within the range of 8 to 10:1 and controls the N content below 100 ppm, thereby improving the performance of the steel and reducing the production cost from an economic perspective. In addition, excessive nitrogen content will affect the plasticity and toughness of the steel and easily cause early fatigue of the metal, resulting in fracture failure of the steel.
[0075] Rare earth elements such as V and Nb are nitrogen-fixing elements, and have a strong ability to bind to N. N in VN steel increases the driving force for the precipitation of vanadium carbonitride V (C, N) particles, promotes the precipitation of vanadium carbonitride, and V element precipitates in the form of V (C, N) precipitation phase and is dispersed in the steel.
[0076] Through VN alloying, carbonitride rare earth compounds are precipitated and dispersed in the grains of the material's base phase structure, which improves the precipitation strengthening effect of the alloy elements. The precipitated particles have a pinning effect on dislocations, thereby hindering the movement of dislocations, thereby improving the steel's deformation resistance and increasing the material's tensile strength and yield strength.
[0077] In the present invention, during the austenitization of steel, V and N are alloyed to precipitate V (C, N) particles, which are distributed in austenite grains and induce ferrite nucleation in austenite crystals. Under the action of phase transformation, a large number of ferrite grains are formed, thereby achieving the purpose of grain refinement. Grain refinement strengthens the area of grain boundaries, so that under the action of external forces, the plastic deformation of the material is more uniform, and the stress concentration is smaller, so the yield strength and plastic toughness of the material can be improved. In addition, grain refinement can also hinder the movement of dislocations and the expansion of cracks, thereby hindering the generation and expansion of material cracks.
[0078] Compared with the prior art, the invention has the following beneficial effects: 1. The hardness and mechanical properties of the raw materials in the normalized state are significantly improved; 2. Through the bending fatigue test of the hub bearing unit product, it is verified that the improvement of material strength significantly improves the fatigue performance of the bearing structure, and the fatigue performance of the structure is improved by more than 80%. 3. The grain refinement effect is obvious, and the grain size grade is improved by 1 level or more.
[0079] Those skilled in the art will appreciate that the above-mentioned embodiments are specific examples for implementing the present disclosure, and in actual applications, various changes may be made thereto in form and detail without departing from the scope of the present disclosure.
Claims
1. A structural steel, characterized in that: In terms of mass percentage, it includes: 0.2.~0.60wt% C, 0.15~0.45wt% Si, 0.6~0.90wt% Mn, 0.10~0.20wt% Cr, 0.10~0.20wt% Ni, 0.01~0.05wt% Al, 0~0.014wt% N, 0.05~0.15wt% rare earth elements, the balance being iron and unavoidable impurity elements; The rare earth element includes V or Nb; The structural steel structure includes a base phase and a strengthening phase, the strengthening phase is dispersed in the base phase, the base phase includes pearlite grains and ferrite grains, the size of the pearlite grains is 25-35 μm, and the strengthening phase includes vanadium carbonitride.
2. A structural steel according to claim 1, characterized in that: The content of N is 0.007-0.014 wt %, and the content of the rare earth element is 0.10-0.15 wt %.
3. The structural steel according to claim 1, characterized in that: The mass ratio of the rare earth element to the N is 8 to 10:
1.
4. The structural steel according to claim 1, characterized in that: The tensile strength of the structural steel is 799-880 MPa, the yield strength is 503-537 MPa, and the elongation is 15.7-23%.
5. A method for preparing structural steel, characterized in that: The steps include: The iron-containing raw material is smelted, and ferrosilicon alloy, ferrochrome alloy, ferromanganese alloy and rare earth alloy are added in the steel tapping process, and the steel tapping is followed by degassing, billet casting and rolling to obtain structural steel, wherein the base phase in the structure of the structural steel has a strengthening phase of vanadium carbonitride distributed therein; The chemical composition of the structural steel comprises 0.2 to 0.60 wt% carbon, 0.15 to 0.45 wt% silicon, 0.6 to 0.90 wt% manganese, 0.10 to 0.20 wt% chromium, 0.10 to 0.20 wt% nickel, 0.01 to 0.05 wt% aluminum, 0 to 0.014 wt% nitrogen, 0.05 to 0.15 wt% rare earth elements, and the remainder is iron and unavoidable impurity elements.
6. A method for preparing structural steel according to claim 5, characterized in that: A slag-removing agent is added during the smelting process, and the slag-removing agent includes a desulfurizing agent and / or a dephosphorizing agent.
7. The method for preparing structural steel according to claim 5, characterized in that: The smelting process further includes refining, and during the refining process, the carbon content is controlled to be 0.50-0.60wt%, the silicon content is controlled to be 0.25-0.45wt%, the manganese content is controlled to be 0.60-0.90wt%, and the chromium content is controlled to be 0.10-0.20wt%.
8. A method for preparing structural steel according to claim 7, characterized in that: The smelting process further includes refining, and during the refining process, the carbon content is controlled to be 0.50-0.60wt%, the silicon content is controlled to be 0.25-0.45wt%, the manganese content is controlled to be 0.60-0.90wt%, and the chromium content is controlled to be 0.10-0.20wt%.
9. The method for preparing structural steel according to claim 5, characterized in that: In the degassing step, the oxygen is controlled to be ≤8ppm and the hydrogen is controlled to be ≤3ppm.
10. The method for preparing structural steel according to claim 5, characterized in that: The starting rolling temperature during the rolling process is 1050-1150° C., the rolling time is 0.5-1h, and the rolling reduction ratio is greater than 15.
Citation Information
Patent Citations
High strength level non-quenched-tempered steel bar for manufacturing of engine rocker and manufacture method thereof
CN110184527A
Steel for cold forging of universal joint fork of passenger car and manufacturing method of steel
CN112853211A
High-strength and high-toughness vanadium-nitrogen microalloyed hot-rolled steel tube and manufacturing method thereof
CN113025915A
Advanced high-strength steel with good fatigue performance and preparation method thereof
CN114622137A
Rare earth carbonitride precipitation strengthened high-strength hot-rolled anti-seismic HRB640E steel bar and preparation method thereof
CN117127115A